Tabu Pangan, Keberagaman Makanan dan Prevalensi Kurang Energi Kronis pada Ibu Hamil di Pedesaan Indonesia - Dudung Angkasa; Dwi Nastiti Iswarawanti; Otte Santika (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Chronic energy deficiency is strongly associated with poor pregnancy outcomes. Food taboo and dietary diversity are suspected as main risk factors of chronic energy deficient in pregnant women in rural area. Nevertheless, none studies elaborated the inferential relationship of those factors with chronic energy deficiency during pregnancy. Purpose: to describe dietary diversity score and perception of food taboo and examine it association with chronic energy deficiency prevalence in pregnant women in a rural area Methods: This cross-sectional study involved 178 pregnant women aged 15-45 years. Food taboo and dietary diversity scores was drawn from single 24 hours food recall while the perceived reason of food taboo was assessed by focus group discussion. Chronic energy deficiency was determined by mid-upper arm circumference by standard tape. Food taboo and dietary diversity score interaction was generated and binary logistic regression analysis with Î±= 5% and 95% confidence interval were performed to provide adjusted associations Results: Almost half of respondents had food taboo (43.8%) and had low dietary diversity score (43%) while one of fifth (19.7%) of respondent were chronic energy deficient. Those with food taboo and low dietary diversity were two times more likely to suffer from chronic energy deficiency. However, only pregnancy related factor (parity) was associated significantly with the outcome. Conclusions: Although the relationship between food taboo and chronic energy deficiency was not statistically significant, pregnant mother with food taboo should be encouraged to have a cultural-specific health and nutrition education.